Effect of low-dose enflurane on the ventilatory response to hypoxia in humans. - Nagyova, B; Dorrington, K; Robbins, P (1994)
To investigate the effects of enflurane on the control of breathing we have studied the ventilatory responses to isocapnic hypoxia in 12 adults with and without sedation with enflurane. Design 1 consisted of three steps into hypoxia (PE' O2 = 6.7 kPa), each lasting 3 min, separated by periods of euoxia lasting 5 min (PE' O2 = 13.3 kPa). Design 1 was repeated four times in each subject on the same day in random order: with carrier gas (control) and with 0.04 MAC, 0.07 MAC and 0.13 MAC of end-tidal enflurane concentrations. Design 2 consisted of 20-min exposures to hypoxia with and without 0.07 MAC of enflurane. Each exposure was preceded and followed by 5 min of euoxia. End-tidal PCO2 was held constant at 0.13-0.27 kPa greater than the resting level throughout both designs. Mean (SEM) ventilatory responses to hypoxia for design 1 were: 8.2 (1.3) litre min-1 (control), 6.6 (1.4) litre min-1 (0.04 MAC), 5.7 (1.1) litre min-1 (0.07 MAC) and 3.7 (0.5) litre min-1 (0.13 MAC) (P < 0.001). For design 2, enflurane produced a 15% reduction in resting ventilation (P < 0.01), a 40% decrease in the acute ventilatory response to hypoxia (P < 0.01) and a 32% reduction in ventilatory decline (ns) which occurred during sustained hypoxia.